The diagnostic utility of FNAC in palpable lesions of breast at a tertiary care centre - Anubha Pandey; K.B. Mishra; Bindu Singh Gaur; Roma Singh (International Journal of Medical Research and Review, 2017)
Background: Breast lumps constitute a significant proportion of surgical cases in both developed and developing countries. Fine Needle Aspiration Cytology (FNAC) is a simple, minimally invasive, cost effective, outpatient based and a rapid diagnostic method for breast lesions. The aim of the present study was to study the cytological spectrum, cytohistological correlation and diagnostic accuracy of aspiration cytology (FNAC) in palpable breast lesions. Material andMethods: This was a prospective study done in the department of Pathology, L.N. medical college, Bhopal, India from January 2016 to December 2016. FNAC of 300 cases of palpable breast lesions were done and reported by expert pathologist. The histopathological specimen when available were reported by other pathologist without prior knowledge. Sensitivity, specificity and accuracy of FNA diagnosis were then analyzed.Results: A total of 300 cases of breast lesion were diagnosed on FNA, out of them histopathological correlation was available for 150 cases. Benign breast lesions are more common in younger patients in 11-30 age group and Malignant breast lesion are more common in old age group patients of 41-60 yrs age group. Benign breast lesions were found in 215 cases (71.66%); among which fibroadenoma (41%) was the commonest lesion observed. Malignancy was observed in 63 cases (21%); among them, Ductal carcinoma was the predominant lesion (17.66%). The sensitivity, specificity and diagnostic accuracy of FNAC for malignant lesion is found to be 98.3%, 98.9% and 98.7% respectively.Conclusion: FNAC is an effective and valid tool as first line diagnostic modality in preoperative diagnosis of malignant and benign breast lesions.